Some unpleasant consequences of testing at length - Giorgio Brunello; Angela Crema; Lorenzo Rocco (Global Labor Organization (GLO), 2018)
Using Italian data on standardized test scores, we show that the performance decline associated with question position is heterogeneous across students. This fact implies that the rank of individuals and classes depends on the length of the test. Longer tests may also exhibit larger gaps between the variance of test scores and the variance of underlying ability. The performance decline is correlated with both cognitive and non-cognitive abilities and there is also evidence that those with better parental background experience a smaller decline than those with poorer background. Therefore, the gap between the two groups widens in longer tests.
Keywords: I21; 330; low stake tests; position of questions; cognitive and non-cognitive skills; Italy